An Analysis of the Optimal Switching Problem in Transmission Systems - Flores, Moises [UNESP] (2017)
This paper presents an analysis of the optimal transmission switching problem. Previous works have reported that opening a transmission line may result in the improvement of the economical operation of the electrical power system. On the other hand, experimental tests have shown that solutions provided by optimization techniques require the disconnection of a relatively large number of lines. In this context, we propose a strategy to efficiently limit the number of lines that should be disconnected to improve the operation of an electrical power system as well as to preserve the reliability of the transmission network. Furthermore, a first attempt is carried out to understand why line disconnections can lead to the enhancement of the operation of transmission systems.